Students’ Motivation in Learning English through Hybrid Learning during Covid-19 Pandemic at Vocational High School - Ka bai (Institut Agama Islam Negeri Palopo, 2022)
This study investigated the students' motivation in learning English through hybrid learning during the Covid-19 pandemic. The data needed in the study was numerical, hich analyzed descriptively. The population of the study was 708 students of the Private Senior Vocational School Muhammadiyah 2 Makassar in the academic year of 2021/2022. The sample of the research was 10% of the population, namely 70 students derived randomly. The data were collected through a questionnaire, compiled by using the Likert scale system. The data were analyzed in frequency, percentage, and mean score.The results showed that the student’s motivation in learning English through the implementation of hybrid learning during the Covid-19 pandemic at SMK Muhammadiyah 2 Makassar was classified as a high category.